Theological education in the Evangelical tradition - Hart, Darryl G.; Mohler, R. Albert, 1959- (Grand Rapids, MI Baker, 1996)
Includes bibliographical references and index.
Keywords: Theology -- study and teaching -- history; Evangelicalism -- history